The development of a predictive model of graft function in uncontrolled donors after circulatory death: validity of a pulsatile renal preservation machine cut-off value for kidney acceptance. Issue 3 (6th August 2018) - Gelpi, Rosana; Paredes, David; Rodríguez-Villar, Camino; Roque, Rebeca; Ruiz, Angel; Adalia, Ramon; Peri-Cusí, Luis; Sole, Manel; Oppenheimer, Federico; Diekmann, Fritz
Abstract: Background: The criteria for kidney suitability in uncontrolled donors after circulatory death (uDCD) procured after regional normothermic perfusion are based on macroscopic appearance and renal haemodynamic values with final renal resistance (FRR). However, these criteria have not been analysed to predict the future graft function. This study presents a model to predict the outcome in uDCD kidneys and define the predictive FRR value. Methods: All uDCD kidney transplants performed in our hospital from 2004 to 2016 were included. Donors and recipients and pre-transplantation data are described. The endpoint was glomerular filtration rate (GFR) ≥30 mL/min at 6 months after transplantation. Results: A total of 194 recipients were included. FRR in donors ≥60 years old was (mean ± SD) 0.27 ± 0.11 versus 0.22 ± 0.09 mmHg/mL/min in donors <60 years (P = 0.042). Kidney survival was 88.2% versus 84% at 12 months and 60.7% versus 30.8% at 120 months (P = 0.067). For the group of recipients from donors ≥60 years, the FRR was 0.37 ± 0.08 mmHg/mL/min in the GFR <30 mL/min group versus 0.18 ± 0.06 mmHg/mL/min in the GFR ≥30 mL/min group (P < 0.001). The value FRR ≥0.3 mmHg/mL/min predicts 59–79% of GFR <30 mL/min [odds ratio = 2.16, 95% confidence interval (CI) 1.80–6.40; P < 0.001]. The predictive accuracy of FRR for GFR by ROC curve was 0.968 (95% CI). The best cut-off for FRR was 0.3 mmHg/mL/min to predict GFR at 6 months with a sensitivity of 67%, specificity of 100%, positive predictive value of 83% and negative predictive value of 92%. Conclusions: Our results suggest that in uDCD donors the combination of donor age ≥60 years together with FRR ≥0.3 mmHg/mL/min could predict poor outcome at 6 months after transplantation in low immunological risk recipients.